Improving Students’ Vocabulary Mastery Using Liveworksheet Website At SMPN 7 Palopo - Fauzia Iksan, Fauzia Iksan; Wahibah, Wahibah; Nurhayati Usman, Nurhayati Usman (Universitas Pakuan, 2025)
This study explores how digital learning tools can transform vocabulary learning through the Liveworksheet website at SMPN 7 Palopo. Conducted as a pre-experimental study with a one-group pre-test and post-test design, the research involved 23 ninth-grade students selected purposively from a population of 60. Using a vocabulary test as the main instrument and SPSS 29 for analysis, the study uncovered a remarkable improvement in students’ vocabulary mastery. The average post-test score (73.04) demonstrated a substantial increase from the pre-test average (38.91), confirming the positive impact of the intervention. Specifically, vocabulary growth was observed across noun, verb, and adjective categories, with mean scores in each category nearly doubling after the treatment. Statistical analysis revealed a t-value (17.201) far exceeding the t-table (2.074), reinforcing the significance of the results. These findings highlight that the Liveworksheet website not only enhances vocabulary acquisition but also fosters interactive and independent learning. Ultimately, this study underlines the potential of technology-integrated platforms like Liveworksheet to make English learning more engaging, accessible, and effective for students in the digital era.